2016
DOI: 10.1038/labinvest.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endotoxin-induced airway epithelial cell injury by a novel family of pyrrol derivates

Abstract: Inflammation and apoptosis are crucial mechanisms for the development of the acute respiratory distress syndrome (ARDS). Currently, there is no specific pharmacological therapy for ARDS. We have evaluated the ability of a new family of 1,2,3,5-tetrasubstituted pyrrol compounds for attenuating lipopolysaccharide (LPS)-induced inflammation and apoptosis in an in vitro LPS-induced airway epithelial cell injury model based on the first steps of the development of sepsis-induced ARDS. Human alveolar A549 and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Results on the inflammatory response of the developed model to a classic inflammatory hit (i.e., LPS) modeling ARDS were in line with what has been observed in previous in vitro and in vivo studies (Huh et al, 2018;Voiriot et al, 2017;Li et al, 2020;Cabrera-Benítez et al, 2016;Peñuelas et al, 2013). As expected, the inflammatory response observed in the advanced model was attenuated, indicating that the presence of LMSCs and the incorporation of different biophysical stimuli play a protective role in response to an endotoxin hit.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results on the inflammatory response of the developed model to a classic inflammatory hit (i.e., LPS) modeling ARDS were in line with what has been observed in previous in vitro and in vivo studies (Huh et al, 2018;Voiriot et al, 2017;Li et al, 2020;Cabrera-Benítez et al, 2016;Peñuelas et al, 2013). As expected, the inflammatory response observed in the advanced model was attenuated, indicating that the presence of LMSCs and the incorporation of different biophysical stimuli play a protective role in response to an endotoxin hit.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, there is an urgent need to develop models with higher physiological relevance to understand the inflammatory processes related to ARDS, the impact of cell therapy ( Nonaka et al, 2020 ), and the use of anti-inflammatory drugs ( Trivedi, Verma, and Kumar 2020 ). Conventional ARDS in vitro models mainly involve applying an inflammatory hit (usually by a bacteriotoxin) to a monolayer of pulmonary epithelial or endothelial cells ( Cabrera-Benítez et al, 2016 ). These conventional models do not fully mimic the complex three-dimensional microarchitecture or the extracellular matrix ( Burgess et al, 2016 ) (ECM) stiffness experienced by cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…43,45 Studies have shown that endotoxin could significantly induce cell apoptosis in cells and animal models. [46][47][48] Endotoxin induces cell apoptosis mainly by stimulating the vascular cells to induce noncalcium-dependent inducible nitric oxide synthase (iNOS) for production of large amounts of nitric oxide (NO) to activate monocytes, macrophages, and neutrophils for release of cytokines such as TNF-α and further to promote the expression of apoptosis-related receptors, such as Fas, TLR-2, CD14, etc. 49 Another study showed that endotoxin could increase the activities of caspases-1 and -3, induced the cleavage of focal adhesion kinase (FAK), and increase the expressions of the proapoptotic protein Bax and p53.…”
Section: Endotoxin Tolerance and Apoptosis Of Immune Cellsmentioning
confidence: 99%
“…Accordingly, LPS from P. aeruginosa is frequently used in in vivo studies of induced acute lung injury. In vitro , it has been shown for example that LPS-exposed A549 (alveolar) and BEAS-2B (bronchial) cells display morphological changes, cell apoptosis and reduced cell survival (Cabrera-Benítez et al, 2016); these effects were attenuated by pyrrole compounds, which also dampened the inflammatory response. In addition, Yi et al showed that LPS induced a decrease in corneal transepithelial resistance, through tight junction disruption, by targeting ZO-1 and ZO-2 proteins (Yi et al, 2000).…”
Section: Evidence For Epithelial Integrity Alterations By Pseudomonasmentioning
confidence: 99%